Religion, Media and Peacebuilding: How does Buddhist TV Promote Harmony between Religious Followers in Malang - Bakhruddin Fannani; Moh. Anas Kholish (Peradaban Journal of Religion and Society, 2022)
This article aims to examine the role and efforts of Dhamma TV, a Buddhist-based television station in Malang City, in building peace and harmony between religious communities. The study also shows the normative-theological construction that underlies these efforts. Because religion and media have great potential for peacebuilding. However, both can also be an obstacle to peace. Thus, religion-based media that consistently strives for harmony and peace become a significant aspect of a pluralistic society. This study found that Dhamma TV is a religion-based media that consistently broadcasts programs that contain the values of togetherness, tolerance, and peace. Television avoids programs that contain violence and have the potential to break the unity and harmony of society. Dhamma TV commonly presents cultural programs and social activities from various religions, so it is considered a medium for interfaith adhesives. The effort to build peace and harmony between religious communities is an expression and implementation of Buddhist teachings. Buddhism emphasizes mutual love and kindness to all living beings. In addition, Buddha emphasizes valuing and respecting the lives of others as his own as well.